2014
DOI: 10.1016/j.ijgo.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of “fresh” versus “macerated” as accurate markers of time since intrauterine fetal demise in low‐income countries

Abstract: Objective To compare provider assessment of fetal maceration with death-to-delivery interval to evaluate the reliability of appearance as a proxy for time of death. Methods Cohort chart abstraction was performed for all stillbirth deliveries at or above 28 weeks of gestation during a 1-year period in a teaching hospital in Ghana. Results Of 470 stillborn infants, 337 had adequate data for analysis. Of 47 fetuses alive on admission with death-to-delivery intervals estimated to be less than 8 hours (expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 18 publications
3
66
0
Order By: Relevance
“…Third, we acknowledge the suboptimal dating criteria for estimation of gestational age due to late presentation to antenatal care and limited ultrasound availability in our setting. Finally, the definitions of antepartum and intrapartum stillbirth are determined by observation at the time of delivery, and previous studies have indicated that this method may overestimate intrapartum stillbirths . That the association between prior CD and both types of stillbirths remained consistent is reassuring, and suggests that such biases may have had minimal impact.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we acknowledge the suboptimal dating criteria for estimation of gestational age due to late presentation to antenatal care and limited ultrasound availability in our setting. Finally, the definitions of antepartum and intrapartum stillbirth are determined by observation at the time of delivery, and previous studies have indicated that this method may overestimate intrapartum stillbirths . That the association between prior CD and both types of stillbirths remained consistent is reassuring, and suggests that such biases may have had minimal impact.…”
Section: Discussionmentioning
confidence: 99%
“…Classification in pre- and intra-hospital stillbirths was a useful, more achievable, and simple alternative to ‘fresh’ versus ‘macerated’ stillbirths, which, as in a study from Ghana, was found unreliable [55]. Moreover, intra-hospital stillbirths may be seen as an even stronger indicator of intra-hospital quality of care than ‘fresh’ stillbirths.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal events included stillbirth, perinatal death and neonatal death. Stillbirth was classified as macerated where the fetus showed skin and soft tissue changes suggesting death occurred before the start of the delivery, and fresh where the fetus lacked such skin changes. Neonatal deaths were divided into early (within 7 days after delivery) and late (between 8 and 28 days after delivery) deaths.…”
Section: Methodsmentioning
confidence: 99%